2020
DOI: 10.1111/aas.13549
|View full text |Cite
|
Sign up to set email alerts
|

Swedish intensivists’ experiences and attitudes regarding end‐of‐life decisions

Abstract: Background To make end‐of‐life (EOL) decisions is a complex and challenging task for intensive care physicians and a substantial variability in this process has been previously reported. However, a deeper understanding of intensivists’ experiences and attitudes regarding the decision‐making process is still, to a large extent, lacking. The primary aim of this study was to address Swedish intensivists’ experiences, beliefs and attitudes regarding decision‐making pertaining to EOL decisions. Second, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…End‐of‐life (EOL) issues within intensive care continues to be in focus and have been discussed several times in this journal since one of the first papers appeared more than 25 years ago 1 . More recently it was found that intensivists from Sweden wish to make EOL decisions based on sufficient information like prognosis and broad consent including family 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…End‐of‐life (EOL) issues within intensive care continues to be in focus and have been discussed several times in this journal since one of the first papers appeared more than 25 years ago 1 . More recently it was found that intensivists from Sweden wish to make EOL decisions based on sufficient information like prognosis and broad consent including family 2 …”
mentioning
confidence: 99%
“…Limitation of life-sustaining treatment in the ICU: We need more knowledge End-of-life (EOL) issues within intensive care continues to be in focus and have been discussed several times in this journal since one of the first papers appeared more than 25 years ago. 1 More recently it was found that intensivists from Sweden wish to make EOL decisions based on sufficient information like prognosis and broad consent including family 2 A study presented in this issue of AAS analyses predictors of limitations of life-sustaining treatment (LST) in Finnish ICUs during 2016. 3 Three types of LST were studied: withholding treatment (WH) at admission or during the ICU stay or withdrawal (WD) during the ICU stay.…”
mentioning
confidence: 99%
“…This qualitative study adheres to the Consolidated Criteria for Reporting Qualitative Research guidelines 15 . This study is a substudy of a previously conducted interview study from our group 14 …”
Section: Methodsmentioning
confidence: 99%
“…Physician‐related variability was mostly unquestioned by the respondents. The leading causes of physician‐related variability were identified as the intensivists' personality as well as their personal and professional experiences 14 …”
Section: Introductionmentioning
confidence: 99%
“…14 Consensus among the entire clinical team is one of the first and most important steps in withholding/withdrawal of non-beneficial treatments for ICU clinicians, who are at higher risk of moral distress and burnout. 41,[46][47][48] Patients admitted to ICU are usually not able to express their preferences about end of life care directly. 16 Therefore, intensivists have to acknowledge any advance directive and interact with patient's surrogate decision maker and family.…”
Section: End Of Life Decision Makingmentioning
confidence: 99%